2006
DOI: 10.1093/bja/ael149
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection with volatile anaesthetic agents during coronary artery bypass surgery: a meta-analysis

Abstract: Previous studies have investigated the role of volatile anaesthetic agents in myocardial protection during coronary artery bypass graft (CABG) surgery, and some have identified beneficial effects. However, these studies have been too small to identify a significant effect on myocardial infarction (MI) or mortality. We undertook a systematic overview and meta-analysis of all randomized trials comparing volatile with non-volatile anaesthesia in CABG surgery. We identified 27 trials that included 2979 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
119
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(128 citation statements)
references
References 58 publications
(11 reference statements)
1
119
1
7
Order By: Relevance
“…9 When compared with intravenous anesthesia, sevoflurane has been shown to reduce the incidence of MI and intensive care unit stay, the length of time on mechanical ventilation following cardiac surgery, in-hospital mortality, and long-term cardiac events. [10][11][12][13][14] The effect of sevoflurane as a cardioprotective agent has not been shown in all studies, 15 and results were also dependent on duration of administration, number of exposures, and dose. For instance, in one study, the beneficial effects were observed only when administered throughout the surgery and not when administered in a fashion similar to ischemic conditioning, before cardiopulmonary bypass, or following the creation of the coronary anastomosis.…”
Section: Résumémentioning
confidence: 91%
“…9 When compared with intravenous anesthesia, sevoflurane has been shown to reduce the incidence of MI and intensive care unit stay, the length of time on mechanical ventilation following cardiac surgery, in-hospital mortality, and long-term cardiac events. [10][11][12][13][14] The effect of sevoflurane as a cardioprotective agent has not been shown in all studies, 15 and results were also dependent on duration of administration, number of exposures, and dose. For instance, in one study, the beneficial effects were observed only when administered throughout the surgery and not when administered in a fashion similar to ischemic conditioning, before cardiopulmonary bypass, or following the creation of the coronary anastomosis.…”
Section: Résumémentioning
confidence: 91%
“…[3][4][5] In the current issue of the Journal, Ansley et al have pursued a different approach: They report the results of their clinical Phase 2 trial (PRO-TECT II) that assessed the impact of administering a targeted dose of systemic propofol during the ischemia-reperfusion interval in patients undergoing heart surgery. 6 They hypothesized that the antioxidant properties of propofol impart anesthetic preconditioning and protect ischemic myocardium from oxidative injury during cardiac surgery.…”
mentioning
confidence: 99%
“…In juxtaposition to Ansley et al, several meta-analyses have demonstrated trends toward more favorable outcomes with inhalation anesthetics. [3][4][5] Yu and Beattie assessed a heterogeneous group of studies that demonstrated a trend toward decreased mortality with inhalation anesthetics. 3 Sevoflurane and desflurane, but not isoflurane, were associated with a decrease in postoperative troponin levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations